2017
DOI: 10.4155/bio-2017-5000
|View full text |Cite
|
Sign up to set email alerts
|

The 10th GCC Closed Forum: Rejected Data, GCP in Bioanalysis, Extract Stability, BAV, Processed Batch Acceptance, Matrix Stability, Critical Reagents, Eln and Data Integrity and Counteracting Fraud

Abstract: The 10th Global CRO Council (GCC) Closed Forum was held in Orlando, FL, USA on 18 April 2016. In attendance were decision makers from international CRO member companies offering bioanalytical services. The objective of this meeting was for GCC members to meet and discuss scientific and regulatory issues specific to bioanalysis. The issues discussed at this closed forum included reporting data from failed method validation runs, GCP for clinical sample bioanalysis, extracted sample stability, biomarker assay va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Thus, development of prescribed guidance for bioanalysis of biomarkers presents a great challenge, and the pace has been understandably slow. In the interim, several articles and White Papers have been published to attempt to fill the gap [12,13,[15][16][17][18][35][36][37]. In 2017, the Biomarker Assay Collaborative Evidentiary Considerations Writing Group, which includes contributing authors from US FDA, published what is known as the C-Path White Paper [23].…”
Section: Small Biomarkers By Lcms Biomarker Assay Validation For Small Molecule Biomarkers By Lcms: Alignment Between the Recommendationsmentioning
confidence: 99%
“…Thus, development of prescribed guidance for bioanalysis of biomarkers presents a great challenge, and the pace has been understandably slow. In the interim, several articles and White Papers have been published to attempt to fill the gap [12,13,[15][16][17][18][35][36][37]. In 2017, the Biomarker Assay Collaborative Evidentiary Considerations Writing Group, which includes contributing authors from US FDA, published what is known as the C-Path White Paper [23].…”
Section: Small Biomarkers By Lcms Biomarker Assay Validation For Small Molecule Biomarkers By Lcms: Alignment Between the Recommendationsmentioning
confidence: 99%
“…Attendees informed the GCC membership that deficiencies were also being received requesting that the whole blood stability be tested in this way. Discussions concerning bioanalytical laboratories' reactions to this Notice began at the 10th GCC Closed Forum [8], occurred as part of the 2016 and 2017 Workshop on Recent Issues in Bioanalysis [19,20] and continued at this Forum. A survey released to CRO and Pharma participants indicated that, prior to this Notice, 70% of respondents exposed a single tube to stability conditions and then assayed at least three replicates from this tube.…”
Section: Matrix Stability Evaluationsmentioning
confidence: 99%
“…The GCC was created in 2010 as an independent global consortium bringing together many CRO leaders to discuss various topics and challenges on scientific and regulatory issues related to bioanalysis [1]. Since its formation, GCC has held regular meetings and published conference reports to share discussions and opinions [2][3][4][5][6][7][8][9][10]. White Papers on specific topics of widespread interest in bioanalysis have also been published to provide unified GCC recommendations helpful to the Global Bioanalytical Community [11][12][13][14][15][16][17][18].…”
mentioning
confidence: 99%